Probabilistic Description Logic Programs - Lukasiewicz, T (Springer, 2005)
Towards sophisticated representation and reasoning techniques that allow for probabilistic uncertainty in the Rules, Logic, and Proof layers of the Semantic Web, we present probabilistic description logic programs (or pdl-programs), which are a combination of description logic programs (or dl-programs) under the answer set semantics and the well-founded semantics with Poole's independent choice logic.We show that query processing in such pdl-programs can be reduced to computing all answer sets of dl-programs and solving linear optimization problems, and to computing the well-founded model of dl-programs, respectively. Furthermore, we show that the answer set semantics of pdl-programs is a refinement of the well-founded semantics of pdl-programs.